Discretionary Disclosure in Financial Reporting: An Examination Comparing Internal Firm Data to Externally Reported Segment Data - Bens, Daniel A.; Berger, Philip G.; Monahan, Steven J. (The Accounting Review, 2011)
ABSTRACT: We use confidential, U.S. Census Bureau, plant-level data to investigate aggregation in external reporting. We compare firms’ plant-level data to their published segment reports by grouping a firm’s plants that share the same four-digit SIC code into a “pseudo-segment.” We then determine whether each pseudo-segment is disclosed as an external segment, or whether it is subsumed into a different business unit for external reporting purposes. We show that a pseudo-segment is more likely to be aggregated when the agency and proprietary costs of separately reporting the pseudo-segment are higher and when firm and pseudo-segment characteristics allow for more discretion in the application of segment reporting rules. For firms reporting multiple external segments, aggregation of pseudo-segments is driven by both agency and proprietary costs. For firms reporting a single external segment, we find no evidence of an agency cost motive for aggregation.